Tuberculose latente em pacientes com artrite reumatoide. Avaliação da resposta celular e novas estratégias diagnósticas. - SILVA, Daniela Graner Schuwartz Tannus (2010)
The diagnosis of latent tuberculosis (TBIL) in patients with rheumatoid arthritis (RA) has got special importance with the advent of anti tumor necrosis factor (anti-TNF-α) and the arise of cases of active tuberculosis in these patients. The tuberculin skin test (TST) is a test used for more than a century on the diagnosis of TBIL but has limited value in patients with RA. New tests that are based on the production and release of interferon-gamma (IFN-γ) have been studied but its role has not yet been well established in this group of patients. This paper shows a review about the use of anti-TNF-α and its role on the development of tuberculosis, the use of the TST for the diagnosis of TBIL in patients with RA and new tests for diagnosis of TBIL. The review is illustrated with a case of a patient who developed tuberculosis after starting the use of anti-TNF-α. In the sequence, a study comparing the diagnostic TBIL in a group of RA patients by cellular immune response, compared to TST, T.SPOT-TB and measurement of IFN-γ by flow cytometry after stimulation with Hspx and through computed tomography changes consistent with TBIL. It was observed that the response to TST was lower in RA patients (13.5%) than the expected response to the general population. We also observed that the T.SPOT-TB identified a greater number of patients with TBIL compared to PT (36.8%). The IFN-γ in response to Hspx was not statistically different among the groups considered TBIL (TST and / or T.SPOT-TB positives) or NO TBIL (TST and T.SPOT-TB negatives). Finally, HRCT showed changes consistent with TBIL in 52.9% of patients, including eight of the eleven patients with TST and T.SPOT TB negatives. Conclusion: The TST alone is not appropriate for the diagnosis of TBIL. The T SPOT TB showed a higher number of positives results compared to TST but was negative in a large percentage of patients with CT changes highly suggestive of TBIL. HRCT is accessible in most major centers and should be incorporated in the diagnostic strategy of TBIL in patients with RA.